Urban Climate Monitoring System with IoT Data Analytics - Rajasekhara Naidu, G; Venkat ram, N (International Journal of Engineering and Technology, 2018)
Climate monitoring was one of the important thing that should be monitored thoroughly and it plays an important role in every person’s life and his surroundings. Due to the increase of factories, vehicles there are so many drastically changes in the climate like increasing of temperature, humidity and the quality of air. In this paper we are designing a climate monitoring system that which detects temperature, humidity, and monitoring the air-quality. Coming to air quality we are mainly concentrating on detecting carbon-monoxide and some pollutants. The information can be checked with gadgets like PC, versatile, tablet through Thingspeak information examination.